2017
DOI: 10.1039/c7nr05320g
|View full text |Cite|
|
Sign up to set email alerts
|

Bismuth oxyiodide coupled with bismuth nanodots for enhanced photocatalytic bisphenol A degradation: synergistic effects and mechanistic insight

Abstract: Oxygen defects and acceleration of photoinduced charge migration were achieved simultaneously by the fabrication of BiOI with deposited Bi nanodots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 48 publications
2
13
0
Order By: Relevance
“…The band gap energies of the as‐prepared BiOCl 1‐ x Br x ( x = 0, 0.5, 1) were estimated using Tauc's equation αhν = A ( hν − E g ) 2 . The E g values of BiOCl, BiOCl 0.5 Br 0.5 and BiOBr are 3.37, 2.92 and 2.83 eV, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The band gap energies of the as‐prepared BiOCl 1‐ x Br x ( x = 0, 0.5, 1) were estimated using Tauc's equation αhν = A ( hν − E g ) 2 . The E g values of BiOCl, BiOCl 0.5 Br 0.5 and BiOBr are 3.37, 2.92 and 2.83 eV, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the wide band gap energy (E g = 3.0-3.2 eV) of TiO 2 which could only response to UV light and limited its efficient utilization of solar light, searching for non-TiO 2 photocatalysts has become one of the most concerned subjects (1,2). Bismuth-based compounds have lately been found to be one of the promising photocatalysts due to their rich varieties, low or nontoxicity and good UV and visible light photocatalytic activity (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Among these, bismuth oxyhalides (BiOX, X = Cl, Br and I) have demonstrated excellent photocatalytic activity because of their unique layered structures and internal static electric fields which could facilitate separation and transfer of photogenerated electron-hole pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Photocurrent characterization has been widely employed to display the charge separation in heterojunction photocatalysts. The higher peak density implies a higher separation efficiency of the photogenerated carriers, which usually plays a positive role in photoactivity promotion [38]. It can be seen that the photocurrent density of 0.2 Bi-BiOBr/BiPO 4 -3 composite increases sharply upon light irradiation and then rapidly decreases to zero when light is turned off.…”
Section: Resultsmentioning
confidence: 98%
“…It can be seen that a broad characteristic peak is located at 133.1 eV (Figure 2(e)), indicating the presence of PO 4 3in 0.2 Bi-BiOBr/BiPO 4 -3 composite [37]. The XPS spectrum of O 1s can be subdivided into two peaks at about 530.0 eV and 531.3 eV (Figure 2(d)), which are assigned to the lattice oxygen and the hydroxyl groups, respectively [36,38]. Based on XPS spectra and XRD results, it can be concluded that Bi-BiOBr/BiPO 4 composites are successfully fabricated.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 96%
“…Bismuth‐based semiconductor materials are widely recognized as visible‐light‐driven photocatalysts due to their good photochemical response to visible light . Among them, the bismuth molybdate family, including several phases in the Bi–Mo–O system, have been evaluated for environmental purification and remediation .…”
Section: Introductionmentioning
confidence: 99%